gga-mir-133a-3p Regulates Myoblasts Proliferation and Differentiation by Targeting PRRX1 - Guo, Lijin; Huang, Weiling; Chen, Biao; Jebessa Bekele, Endashaw; Chen, Xiaolan; Cai, Bolin; Nie, Qinghua (Frontiers in Genetics, 2018)
Non-coding RNAs play a regulatory role in the growth and development of skeletal muscle. Our previous study suggested that gga-mir-133a-3p was a potential candidate for regulating myoblast proliferation and differentiation in skeletal muscle. The purpose of our study was to reveal the regulatory mechanism of gga-mir-133a-3p in the proliferation and differentiation of chicken myoblasts. Through the detection of cell proliferation activity, cell cycle progression and EdU, we found that gga-mir-133a-3p can significantly inhibit the proliferation of myoblasts. In the process of myogenic differentiation, gga-mir-133a-3p is up-regulated, while gga-mir-133a-3p can significantly promote the up-regulation of differentiation-related muscle-derived factors, indicating that gga-mir-133a-3p can promote the differentiation of myoblasts. Validation at the transcriptional level and protein level proved that gga-mir-133a-3p can inhibit the expression of PRRX1, and the dual-luciferase assay also showed their direct targeting relationship. Correspondingly, PRRX1 can significantly promote myoblast proliferation and inhibit myoblast differentiation. In our study, we confirmed that gga-mir-133a-3p participates in the regulation of proliferation and differentiation of myoblasts by targeting PRRX1.